2004
DOI: 10.1084/jem.20040499
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Release by Transmigrating Neutrophils Deactivates Endothelial-bound SDF-1α and Attenuates Subsequent T Lymphocyte Transendothelial Migration

Abstract: Leukocyte trafficking to sites of inflammation follows a defined temporal pattern, and evidence suggests that initial neutrophil transendothelial migration modifies endothelial cell phenotype. We tested the hypothesis that preconditioning of human umbilical vein endothelial cells (HUVEC) by neutrophils would also modify the subsequent transendothelial migration of T lymphocytes across cytokine-stimulated HUVEC in an in vitro flow assay. Using fluorescence microscopy, preconditioning of HUVEC by neutrophils was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 61 publications
1
59
0
Order By: Relevance
“…50,51 In contrast, results from a later study suggested that neutrophils may inhibit the transmigration of T cells into inflamed sites by elastase-mediated deactivation of endothelium-associated CXCL12. 52 We have recently demonstrated that monocytes regulate the transendothelial migration of neutrophils into lung grafts. 8 Future studies using intravital 2P microscopy will be helpful in defining how neutrophils regulate the trafficking of other cell populations within lungs.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 In contrast, results from a later study suggested that neutrophils may inhibit the transmigration of T cells into inflamed sites by elastase-mediated deactivation of endothelium-associated CXCL12. 52 We have recently demonstrated that monocytes regulate the transendothelial migration of neutrophils into lung grafts. 8 Future studies using intravital 2P microscopy will be helpful in defining how neutrophils regulate the trafficking of other cell populations within lungs.…”
Section: Discussionmentioning
confidence: 99%
“…HUVEC monolayers were stimulated with TNF-␣ (25 ng/mL for 4 hours) and then treated with SDF-1␣ (50 ng/mL; CXCL12) for 15 minutes before insertion into the flow chamber for TEM studies as previously described. 22 This step promotes T-cell TEM. 23 Human CD3 ϩ T cells (Ͼ 90% pure) were isolated by negative selection from anticoagulated whole blood of healthy volunteers as previously described.…”
Section: Human and Murine Endothelial Cell Isolation And Culture And mentioning
confidence: 99%
“…23 Human CD3 ϩ T cells (Ͼ 90% pure) were isolated by negative selection from anticoagulated whole blood of healthy volunteers as previously described. 22 Blood was drawn and handled according to protocols for protection of human subjects approved by the Brigham and Women's Hospital Institutional Review Board, and all volunteer subjects gave informed consent, in accordance with the Declaration of Helsinki. The isolation and culture of murine heart endothelial cells (MHECs) from 7-to 9-day-old pups was performed as described.…”
Section: Human and Murine Endothelial Cell Isolation And Culture And mentioning
confidence: 99%
See 2 more Smart Citations